DETERMINING THE MODERATING EFFECT OF PERCEIVED ENVIRONMENTAL UNCERTAINTY - MANAGEMENT ACOUNTING INFORMATION SYSTEMS RELATIONSHIP IN INDONESIA MANUFACTURING COMPANIES - Kirmizi Ritonga (Indonesian Management and Accounting Research, 2010)
This study examines the effect of perceived environmental uncertainty (PEU) on the design of management accounting information system (MAIS) which is moderated by decentralization. MAIS is design to provide chief executive officers information to make decision, planning, and controlling was defined in terms of the extent to which managers use time information characteristics ofbroad scope, timeliness, and aggregation in manufacturing finns. The study of 158 chief executive officers that have responsible for an organization, drawn from the manufacturing companies in Jakarta, Tangerang, Bogor, and Kerawang. The questionnaire survey, which was analyzed by using a regression analysis, suggests that PEU have an effect on the aggregated MA S information moderated by decentralization.Keywords: PEU, MAIS, Manufacturing Companies, Decentralization